Partnership impact on integrating business strategy: a study on strategic partnership management of The Daily Star - Khokon, Sk. Md. Muttakin (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.